Teach Yourself VISUALLY HTML5: The Fast and Easy Way to Learn - Wooldridge, Mike (John Wiley and Sons, 2011)
Make mark-up language more manageable with this visual guide HTML5 is the next-generation of web standard mark-up language, and among other things, it offers amazing new avenues for incorporating multimedia into your sites. What easier way to master all of HTML5's new bells and whistles than with a guide that shows you, screenshot by screenshot, just what to do? Over a hundred tasks that web designers need to know most are explained using, full-color screenshots and how-to steps. From the easy stuff like revised new header and footer elements to complex updates such as canvas and audio, this guide covers the new, as well as most-commonly used, tags and features. * Helps you get up to speed on the completely redesigned new HyperText Markup Language, HTML5 * Shows you how to incorporate rich media content into the sites you design, without relying on proprietary software such as Flash * Explains revisions, from essential structural elements like header and footer to more complex elements such as canvas and audio over a hundred tasks in all * Uses easy-to-follow, full-color, two-page tutorials, so you can see step by step how to do tasks and quickly obtain the information you need Web designers, keep your HTML skills up to date with this "learn-by-seeing," visual guide.